Metalworking by cutting. Machines and tools : textbook - Moshchenok, Vasyl; Pimonov, Igor; Ptushka, Anastasiia (LAMBERT Academic Publishing, 2025)
The textbook covers the physical fundamentals of cutting materials, tool materials, machining methods and technologies. The first chapter covers movements in metal cutting machines, cutter geometry, chip formation, forces and thermal phenomena during cutting, tool wear and stability, and the procedure for assigning cutting modes. The second chapter is devoted to tool materials. Subsequent chapters cover individual types of machining: turning, drilling, milling, planning, chiselling, broaching, piercing, gear cutting, threading, grinding, and finishing abrasive machining. The section on physical and chemical methods covers electrophysical, electrochemical, ultrasonic and beam processing. The chapter on metal-cutting machines covers their classification, detailed descriptions of various types of machines (turning, milling, grinding, boring, and electrical discharge machining), as well as robotics and computer numerical control (CNC) systems. At the end of the textbook, you will find tests, assignments, and a list of recommended readings to help you consolidate the material.
Keywords: mechanical engineering; production technology